Social Capital Existence in Bali’s Microfinance: Evidence from Village Credit Institution (LPD) - Pera Sundarianingsih; Khusnul Ashar; Putu Mahardika Adi Saputra (Journal of Innovation in Business and Economics, 2018)
Bali has two village governance systems: administrative-village and customary-village. Administrative-village is the extension of government’s authority in administrative aspects. Meanwhile, customary-village (pakraman village) denotes traditional institution that has a function to organize krama (residents) based on the awig-awig (customary law). The role of customary-village is fundamental in carrying on the custom and culture of Bali as well as triggering the economical aspect from the society through Village Credit Institution (LPD). This study is intended to describe the existence of social capital over the LPD by employing inductive-qualitative approach. Social capital over the LPD can improve the societies’ harmony that have been established in advance. Furthermore, the social capital bonding, bridging and linking can be used continuously in social life.